Association Between Earwax-Determinant Genotypes and Acquired Middle Ear Cholesteatoma in a Japanese Population. (January 2022) - Hara, Satoshi; Kusunoki, Takeshi; Nakagawa, Hiroshi; Toyoda, Yu; Nojiri, Shuko; Kamiya, Kazusaku; Furukawa, Masayuki; Takata, Yusuke; Okada, Hiroko; Anzai, Takashi; Matsumoto, Fumihiko; Ikeda, Katsuhisa
Objective: A single-nucleotide polymorphism 538G>A in the human ABCC11 gene is a determinant of the earwax morphotype. ABCC11 538GG and GA correspond to wet earwax and 538AA to dry earwax. Despite a putative positive correlation between the frequency of the 538G allele and the prevalence of cholesteatoma, minimal clinical information is currently available. We aimed to evaluate this association between the ABCC11 genotypes and acquired middle ear cholesteatoma. Study Design: Case-control study. Setting: Single-center academic hospital. Methods: We recruited 67 Japanese patients with acquired middle ear cholesteatoma (cholesteatoma group) and 100 Japanese controls with no history of middle ear cholesteatoma. We assessed the ABCC11 genotypes for all participants. Clinical information was collected from the cholesteatoma group. The genotype data of 104 Japanese people from the 1000 Genomes Project who represent the general population were used. Results: The proportion of participants with ABCC11 538GG or GA was significantly higher in the cholesteatoma group than in the control group or general Japanese population ( P < .001). The ABCC11 538G allele frequency was also significantly higher in the cholesteatoma group than in the control group or general Japanese population ( P < .001). Multivariate logistic regression analyses revealed a significant association between the ABCC11 genotype and acquired middle ear cholesteatoma (odds ratio, 5.49; 95% CI, 2.61-11.5; P < .001). Conclusion: Our results suggest that the ABCC11 genotypes could be associated with the development of acquired middle ear cholesteatoma among Japanese people.